2002
DOI: 10.1074/jbc.m204808200
|View full text |Cite
|
Sign up to set email alerts
|

The Germ Cell-specific Transcription Factor ALF

Abstract: The assembly and stability of the RNA polymerase II transcription preinitiation complex on a eukaryotic core promoter involves the effects of TFIIA on the interaction between TATA-binding protein (TBP) and DNA. To extend our understanding of these interactions, we characterized properties of ALF, a germ cell-specific TFIIA-like factor. ALF was able to stabilize the binding of TBP to DNA, but it could not stabilize TBP mutants A184E, N189E, E191R, and R205E nor could it facilitate binding of the TBP-like factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…The extracts were centrifuged at 14,000 rpm for 15 min to obtain clarified lysates. TBP-dependent mobility shift assays were performed as described (7).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The extracts were centrifuged at 14,000 rpm for 15 min to obtain clarified lysates. TBP-dependent mobility shift assays were performed as described (7).…”
Section: Methodsmentioning
confidence: 99%
“…Earlier results had suggested that ALF and TFIIA were similar with respect to their ability to interact with TBP (7) and that both could support RNA polymerase II activity in vitro (5,6). Even though TFIIA is not normally present in oocytes, we wanted to evaluate whether it could function in this system.…”
Section: Inhibition Of Alf Reduces Polymerase Ii-dependent Transcriptmentioning
confidence: 99%
See 2 more Smart Citations
“…One of these germ cell variants, TFIIA␣/␤-like factor (ALF) 2 (TFIIA), encodes a counterpart of the large subunit of the general transcription factor TFIIA (4 -6). ALF interacts with the small TFIIA␥ subunit to form a complex that can stabilize binding of TBP-like factors to promoter DNA, thereby facilitating formation of a transcription preinitiation complex in germ cells (7,8). The loss of ALF expression is associated with male infertility in humans (9).…”
mentioning
confidence: 99%